Effect of smoking on interleukin 6, tumor necrosis factor and C-reactive protein in hypertensive patients - Ali Saleh, Jawad (Tikrit Journal of Pharmaceutical Sciences, 2023)
Smoking is a main independent risk factor for cardiovascular disease which include hypertension, unstable angina, myocardial infarction, vascular disease, and stroke. The aim of study is to identify the effect of smoking on interleukin 6, tumor necrosis factor alpha and C-reactive protein in smoking and hypertensive patients. Data collected was carried out during the period from July 2018 to September 5,125.72 cm Bajii city which include measurement of Interleukin 6, C.R protein and tumor necrosis factor alpha. In this study there was a significant differences between the control and hypertensive cases, but there is non-significant differences between hypertensive smoker and non-smoker cases. About the interlukin there is a significant differences between the control and hypertensive cases. In C.R protein, there is a significant differences between the control and hypertensive cases, but there is non-significant differences between hypertensive smoker and non-smoker cases, about the tumor necrosis factor, there is a significant differences between the control and hypertensive cases, but there is non-significant differences between hypertensive smoker and non-smoker